Prospects and contradictions concerning social partnership in Russia in the age of globalisation - Gulnara Aitova (Hans-Böckler-Stiftung, 2015)
This book provides an analysis of the contradictory nature of the social partnership system in Russia which was triggered by the process of neoliberal globalization. Being part of the growing economies BRICS and rapidly integrating into the world economy through opening for foreign direct investments coming from leading capitalist countries, especially from Germany, Russia is experiencing the impact of the transition to a market economy on labour relations. This moment ties up with specific features of the Russian history of labour relations, so there is a definite lack in Germany and other countries of knowledge and understanding regarding the Russian labour system. Hence, this study aims to clarify this problem.The book shows that as in other transitional economies a driver of market changes has yet to emerge. In Russia state bureaucracy takes the function of initiator and actor of market reforms. The state has to take part in resolving the contradiction between low labour standards existing in national companies with middle and low levels of capitalization and the developments in multinational corporations which are gradually going ahead to collective conflict resolution. The perspectives in the social partnership in Russia are closely connected with the development of independent trade unions as an equal counterpart.
Keywords: 330; Arbeitsbeziehungen; Sozialpartner; Tarifvertrag; Russland